PENINGKATAN PEMAHAMAN KONSEP BIOLOGI MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) MATA KULIAH BIOLOGI UMUM - Eko Wulandari, S.Pd.I., M.Pd (Pendidikan Matematika | STKIP YM Bangko, 2022)
The background of this research was the lack of understanding of students in the learning process for general biology courses. Meanwhile, general biology learning requires the ability to think critically and understand the material concepts and problems given to students. The learning model used in the learning process for general biology courses has not previously used a learning model that can improve students' understanding. The research method used in this research is Classroom Action Research (CAR). This study aims to improve students' understanding of the material concepts in general biology courses. The results of this study indicate that after the application of the PBL learning model there is an increase in students' understanding of the general biology course, namely in the Organism and Environment material or cycle I, an increase of 55%, and the homeostatic regulation system material in the second cycle, an increase of 90% of students have understood concept of the given material. So it can be concluded that the application of the PBL model can improve students' understanding of biology concepts in general biology courses